The effect of blade density variation to cocopeat mass that produce by Poltesa cocopeat machine - Pande Putu Agus Santoso; Iklas Sanubary; Diah Mahmuda (TURBO [Tulisan Riset Berbasis Online], 2022)
Cocopeat machines that have been developed today, were carried out with variations in the speed of rotation, blade length, blade shape, and treatment of objects (coconut coir immersion). There has been no development of a cocopeat machine that focuses on variations of blade density. It is suspected that the blade density affects to the difference of cocopeat mass produced. This study was a true experiment. The dependent variable was cocopeat mass. The independent variables were blade density, consisting of Ïƒ1 (84/210Ï€), Ïƒ2 (42/210Ï€) and Ïƒ3 (21/210Ï€). For each variation of the independent variable was conducted 10 experiments. The study sample was 30 pieces of coconut coir. The mass of each coconut coir was 50 grams. The engine's spin speed, length and blade shape, are the same for all samples. The data was analyzed using the t test at a significance level of 5%. The average mass values of cocopeat were Ïƒ1 ( Â = 16.5430; S1 = 1.9674), Ïƒ2 ( Â = 12.2650; S2 = 1.8341) and Ïƒ3 (Î¼3 = 10.0988; SD = 1.8943). The t test showed that the difference in the average value of cocopeat mass between groups were to12 = 5,030; to23 = 2,598; and to13 = 7,462. If t-table value for Î½ = 18 was 2,101, so . Ho was rejected and H1 accepted, so there was a difference of cocopeate mass that produced by poltesa cocopeat machine, which is effected by variations of blade density.